A new species of Dixella, the first Mexican record of Dixella shannoni, and a summary of dixid records from Mexico (Diptera: Dixidae) - Huerta, Heron; Ibáñez-Bernal, Sergio (Zootaxa, 2021)
We describe a new species of the genus Dixella Dyar & Shannon of Mexico. Specimens were collected in Lagunas de Santo Domingo, Municipality of Huatusco, Veracruz, a small vegetation-lined lake within an increasingly relictual mountain cloud forest. This species is most closely related to Dixella cumbrica Peters & Cook, 1966, based upon the shape of the apical lobe of the gonocoxite and flattened gonostylus. Also, we include the first record of Dixella shannoni (Lane, 1942), in Mexico, based upon specimens collected in Santiago Yaveo, Oaxaca. Additionally, we present a list of all localities in which dixids have been collected in Mexico.